Effects of β-hydroxy-β-methylbutyrate (HMB) supplementation on lipid profile in adults: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Sadeghi, Behrad; Bahari, Hossein; Jozi, Hannane; Hasanzadeh, Mohammad-Ali; Hashemi, Dorna; Bideshki, Mohammad Vesal (Frontiers in Nutrition, 2024)
The regulation of lipid metabolism is crucial for preventing cardiovascular diseases, which are among the leading causes of mortality worldwide. β-Hydroxy-βmethylbutyrate (HMB) has garnered attention for its potential role in modulating lipid profiles.However, the magnitude of these effects are unclear due to the heterogeneity of the studies. This study aimed to provide a comprehensive overview of the randomized controlled trials (RCTs) that have examined the effects of HMB on lipid profiles in adults.Methods: Databases including PubMed, Web of Science, and Scopus, were searched for relevant studies through January 2024. The study protocol was also registered at Prospero (no. CRD42024528549). Based on a random-effects model, we calculated WMDs and 95% confidence intervals (CIs). The outcomes assessed included total cholesterol (TC), triglyceride (TG), lowdensity lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C).Sensitivity, subgroup and meta-regression analyses were also conducted.Results: Our analysis included a total of 10 RCTs comprising 421 participants. The pooled data revealed no significant effect of HMB supplementation on TC (WMD: -2.26 mg/dl; 95%CI: -6.11 to 1.58; P = 0.25), TG (WMD: -2.83 mg/dl 95% CI: -12.93 to 7.27; P = 0.58), LDL-C (WMD: 0.13 mg/dl; 95%CI: -3.02 to 3.28) mg; P = 0.94), and HDL-C (WMD: -0.78 mg/dl; 95%CI: -2.04 to 0.48; P=0.22). The quality of evidence was rated as moderate to low for all outcomes.The current evidence from RCTs suggests that HMB supplementation does not significantly alter lipid profiles, including TC, TG, LDL-C, and HDL-C. Further research is warranted to confirm these results and explore the potential mechanisms of action of HMB.